Morphometric analysis of mandibular foramen in Saudi children using cone-beam computed tomography - Guna Shekhar Madiraju; Nazargi Mahabob; Sanusi Mohammad Bello (Wolters Kluwer Medknow Publications, 2021)
Objectives: This study evaluated the position of the mandibular foramen (MF) with regard to the occlusal plane (OP) and the anterior border (AB) of the mandibular ramus (AB) in a sample of 7-12-year-old Saudi children using cone-beam computed tomography (CBCT) images. Materials and Methods: In this descriptive, observational study, 155 CBCT scans were selected and analyzed for positional changes in the MF. Reconstructed panoramic and axial sections were used to measure the MF-OP and MF-AB distances, respectively, on both the right and left sides of the mandible. Data were analyzed using paired t-test, independent t-test, one-way analysis of variance, and Tukey's honest significant difference post hoc tests where applicable, at a significance level of P < 0.05. Results: The mean distance of MF from the AB of the ramus was 14.68 mm, with no significant differences between the genders (P > 0.05). The MF moved upward from a position below the OP to above it, according to age in both males and females, and the difference between the age groups was significant (P < 0.05). No significant differences (P < 0.05) in the mean values of distances between the right and left sides of the mandible were seen. Conclusions: The location of the MF varies with respect to age and should be considered while administering inferior alveolar nerve block in children to achieve a more effective anesthesia.